CORRELATION BETWEEN SEMEN EVALUATION PARAMETERS AND FERTILITY OF FROZEN-THAWED SEMEN OF JERSEY X LOCAL HILL CATTLE CROSSBRED BULLS - SHARMA, MRIDU; SINGH, MADHUMEET; SHARMA, AMIT; KUMAR, PRAVESH (The Indian Journal of Animal Reproduction, 2016)
The present study investigated the correlation between semen evaluation parameters and their reliability in predicting the fertility of Jersey X local hill cattle crossbred bulls. Fourty ejaculates (8/bull) of five bulls were subjected to semen evaluation as well as fertility trials. The performance of bulls in terms of analyzed semen parameters was above the acceptable limits, however, none of the parameters was correlated to fertility of these bulls.